Competitive and synergic sorption of carbamazepine, citalopram, clindamycin, fexofenadine, irbesartan and sulfamethoxazole in seven soils - Schmidtová, Zuzana; Kodešová, Radka; Grabicová, Kateřina; Kočárek, Martin; Fér, Miroslav; Švecová, Helena; Klement, Aleš; Nikodem, Antonín; Grabic, Roman (Journal of contaminant hydrology, 2020)
Sorption of pharmaceuticals, which can occur in soils, may differ when present in a soil solution as a single compound or in a solution with other pharmaceuticals. Therefore, the sorption isotherms described by the Freundlich equations were evaluated for 6 compounds, which were applied in solutions of a single pharmaceutical, two pharmaceuticals or all pharmaceuticals to seven soils. Study mainly focused on a behavior of fexofenadine and irbesartan that occurred in soils in 3 forms (cationic, zwitter-ionic or neutral, anionic). Sorption of both compounds slightly increased (in some soils) when applied together, largely increased when applied with carbamazepine (neutral), and extremely increased when applied in solutions with citalopram (strongly sorbed cation), which could be explained by a cooperative multilayer sorption on soil constituents. On the other hand, sorption of both compounds moderately decreased when applied with clindamycin (cation and neutral) or sulfamethoxazole (neutral or anion). The magnitude of an increase or decrease in the Freundlich sorption coefficient (KF) for a particular compound depended on soil conditions, a form of compound's molecule and its interaction with molecules of other compounds. Despite sorption being influenced by other compound(s) in solution, the KF coefficients evaluated for a particular compound under the different conditions were mostly correlated with the same soil properties: KF,CAR with an organic carbon content, KF,CIT and KF,CLI with a base cation saturation, KF,SUL with hydrolytic acidity, and KF,FEX and KF,IRB with sorption complex saturation.
Keywords: Penta-solute solution; Bi-solute; Citalopram; Terfenadine; Soil Pollutants; Adsorption; karbamazepin; irbesartan; Soil types; látky znečišťující půdu; sulfamethoxazol; Sulfamethoxazole; Clindamycin; citalopram; Cooperative multilayer sorption; Irbesartan; Sorption; Pharmaceuticals; Carbamazepine; Soil; Single-solute; půda; terfenadin; adsorpce; klindamycin